#TITLE_ALTERNATIVE# - RIDWAN MALIK (NIM : 13604020); Pembimbing : Dr. Romie O. Bura, DEDEN
Waverider concept was first introduced by Terence Nonweiler in 1951. Until now, however, waverider concept is very difficult to be realized become an aircraft or flight vehicle. One of the difficulties is the integration process between waverider as vehicle airframe and scramjet as propulsion system. This final project discusses design and analysis process of waverider, scramjet inlet, and integration of both. Design and analysis process of waverider are based on general wedge-derived waverider type, while scramjet inlet is based on two-dimensional configuration with one-dimensional flow analysis. Integration process involves design and analysis of waveider and scramjet inlet altogether. Analysis of integrated waveriderÃ‚Â–scramjet inlet is based on two-dimensional configuration of scramjet inlet. To support design and analysis process, program code is developed using C++ with object-oriented programming capability. Using this program code, the alteration effect of waverider and scramjet inlet design variables respect to exergy destroyed rate variable is investigated. The investigation result shows that exergy destroyed rate variable has capability to connect waverider design and analysis process and scramjet inlet design and analysis process. It provides easiness when integration process is taken place.